How do you simplify \frac { c ^ { - 1} } { c ^ { 0} \cdot c ^ { 0} \cdot c ^ { 0} }c1c0c0c0?

1 Answer
Mar 14, 2017

See the entire simplification process below:

Explanation:

First use this rule of exponents to simplify the denominator: a^color(red)(0) = 1a0=1

c^-1/(c^color(red)(0) * c^color(red)(0) * c^color(red)(0)) = c^-1/(1 * 1 * 1) = c^-1/1 = c^-1c1c0c0c0=c1111=c11=c1

Next, use these two rules to complete the simplification:

x^color(red)(a) = 1/x^color(red)(-a)xa=1xa and a^color(red)(1) = aa1=a

c^color(red)(-1) = 1/c^color(red)(- -1) = 1/c^color(red)(1) = 1/cc1=1c1=1c1=1c